Myanmar Media: Legacy and Challenges - Ochwat, Maria (The Age of human rights, 2020)
For nearly fifty years Myanmar was ruled by a military junta. It did not tolerate any criticism, and severely punished anyone who dared to oppose them. At the same time, it cut the country off from the rest of the world, preventing it from being informed about Burma’s internal situation. The announcement of the changes came when Thein Sein’s first civilian government was formed in 2011. Almost 10 years have passed since then and Myanmar, according to the Press Freedom Index, is considered to be one of the countries where freedom of speech and freedom of the media are commonly violated and journalists are often persecuted and punished. Freedom of expression is one of the pillars of a democratic society, the basis for its development and a condition for the self-fulfillment of the individual. One of the most important ways of exercising freedom of speech is through free and independent media. The issue of respect for freedom of expression and freedom of the media must be seen in a broader context. It should be noted that there is a close link between respect for human rights and peacekeeping. Although freedom of expression, and thus freedom of the media, is one of those freedoms which may be restricted in specific situations, it cannot be done arbitrarily. Under public international law the exercise of these freedoms, since it carries with it duties and responsibilities, may be subject to such formalities, conditions, restrictions or penalties as are prescribed by law and are necessary in a democratic society, in the interests of national security, territorial integrity or public safety, for the prevention of disorder or crime, for the protection of health or morals, for the protection of the reputation or rights of others, for preventing the disclosure of information received in confidence, or for maintaining the authority and impartiality of the judiciary. The authorities of Myanmar, when introducing and maintaining restrictions on freedom of speech and media, often invoke the need to restrict freedom of speech and media for reasons of state security, protection of morality or public order. However, one can venture to say that they are in fact afraid of criticism and possible public actions against the current authorities.